Dakwah Kontemporer Kaum Muda Milenial: Komunitas Kereta Hijrah - Agus Firmansyah (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2025)
This study examines modern da'wah among youth via the formation of a hijrah community focused on this objective. The objective is to alter the mentality of young individuals confronting a moral crisis. In addition, this research also faces the challenges presented by the emergence of new media such as Instagram, which can have a huge impact on human cognition. This research uses qualitative methods, specifically visual ethnography, content analysis and desk research, using journals, books and images to validate the data presented. And the results of this study show that the presence of this hijrah community has a very beneficial influence, coupled with the presence of internet media, clarifying a da'wah carried out by young people today, offline and online involvement strengthens a very effective communication or interaction.